Redescription of Parotocinclus haroldoi Garavello, 1988 (Siluriformes: Loricariidae), Northeastern Brazil - Ramos, Telton Pedro Anselmo; Neto, Luciano De Freitas Barros; Ferreira, Karina Carvalho Fernandes; de Lucena Barbosa, José Etham (Zootaxa, 2020)
Parotocinclus haroldoi is separated from most of its congeners by having an abdomen covered by relatively large plates (vs. naked abdomen or with small plates). This species occurs in Parnaíba River basin with two other congeners, P. cabessadecuia and P. cearensis. Parotocinclus haroldoi is distinguished from P. cabessadecuia for having developed adipose fin (vs. rudimentary or absent adipose fin) and P. cearensis, for having abdomen covered by entirely plates (vs. almost naked abdomen with small sparse plates). Parotocinclus haroldoi is known from the Parnaíba river basin in the state of Piauí, Maranhão-Piauí.